Edukasi Tanaman Herbal sebagai Booster ASI di Desa Rindu Hati Kecamatan Taba Penanjung, Bengkulu Tengah - Pratama, Rini Mustikasari Kurnia; Destriani, Sri Nengsi (Jurnal Abdimas Kesehatan (JAK), 2024)
One of the failures of exclusive breastfeeding is the mother’s perception that breast milk production is small or insufficient, giving rise to concerns that the baby will not be able to get enough. Another problem that arises if exclusive breastfeeding coverage is inadequate is nutritional problems and this causes stunting. Efforts made to increase mother’s knowledge about increasing breast milk boosters, where these local plants are Moringa leaves and Kepok banana blossoms. The aim of implementing this educational activity is to change the knowledge of educational participants about the use of local plants as breast milk boosters. The activity will be carried out on October 18, 2023 where the increase in knowledge can be seen from pre-test, given education using prepared materials, and continued post-test. This activity was attended by 22 breasfeeding mothers who have children in Rindu Hati Village, Taba Penanjung District, Central Bengkulu Regency. The evalution result during the activity showed that the participants were very enthusiastic and had active discussions. There was an increase in knowledge of breastfeeding mothers after aducation was conducted about the use of local plants as breast milk boosters in Rindu Hati Village. It is hoped that breastfeeding mothers can apply the knowledge gained so that breastfeeding mothers’ breast milk production increases and reduce mothers’ concerns about low breast milk production by utilizing Moringa leaves and Kepok banana blossoms which are easily available around the home.